2019
DOI: 10.1177/2158244019864175
|View full text |Cite
|
Sign up to set email alerts
|

The U.S. Presidential Election 2012/2016 and Investors’ Sentiment: The Case of CBOE Market Volatility Index

Abstract: Given that political events have substantial effect on new economic policies and economic performance of the country, this article aims to examine the behavior of the investors’ sentiment in terms of implied volatility index trailed by the U.S. presidential elections. The study empirically tests whether the presidential elections in 2012/2016 do contain the important market inclusive information to explain the expected stock market volatility. The findings indicate that investors’ concern was distracted around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…In addition, the choice of time frame becomes even more necessary for research studies that are set in the context of social events. Some examples are the effect of COVID-19 on investor sentiment (Chen et al 2020;Huynh et al 2021) and the effect of political elections on investor sentiment (Oyebode and Orji, 2019;Shaikh, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the choice of time frame becomes even more necessary for research studies that are set in the context of social events. Some examples are the effect of COVID-19 on investor sentiment (Chen et al 2020;Huynh et al 2021) and the effect of political elections on investor sentiment (Oyebode and Orji, 2019;Shaikh, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Following Blau et al (2019), who demonstrated that specific stock prices anticipated the 2016 election outcome, we considered that some sectors may have foreshadowed the possible outcome. Thus, although Hillary Clinton was declared the winner of all three presidential election debates held during September and October-the fact that made Trump's victory a global surprise-still, we decided not to consider the period that encompassed the election debates precisely having in mind that these events might have influenced the expectations of market participants (see Shaikh, 2019). Finally, we use a post-event window of (1, + 10) trading days.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, Shaikh (2019) analyzed the behavior of investor sentiment—measured by the SPX and CBOE VIX indexes—against the background of the 2012 and 2016 U.S. presidential elections. Briefly, the author demonstrated that the U.S. stock market was inefficient during the presidential election period; that is, the market was more turbulent before the Election Day, but in the post-election period, VIX reached its normal level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Risiko politik merupakan salah satu factor penting yang mempengaruhi operasi pasar keuangan suatu negara, bias dating dalam berbagai bentuk seperti kudeta, pemilihan, atau perubahan rezim negara (Kabiru, 2015). Diantara semua peristiwa politik, pergantian pemerintahan dengan proses pemilihan umum merupakan peristiwa yang paling memengaruhi pasar (Shaikh, 2019). Ini karena kebijakan-kebijakan yang dibuat oleh pemimpin baru nantinya akan memengaruhi kondisi ekonomi di masa mendatang dan juga secara tidak langsung akan berdampak pada bursa saham tempat terjadinya peristiwa politik tersebut.…”
Section: Pendahuluanunclassified